ASSESSMENT OF FLOOD RECESSION ON SELECTED MACRO NUTRIENTS AND CHEMICAL PROPERTIES OF SOILS IN SOUTHERN IJAW, BAYELSA - Ozi, V.; Peter, K.D.; Gobo, A.E.; Ngah, S. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out in Southern Ijaw Local Government Area of Bayelsa State, Nigeria with the sole aim to assess the effect of flood recession on soil chemical properties and selected micro nutrients using the Semi detailed soil survey approach. One soil profile pit each was dug in each of the identifiable mapping unit and described in situ. Results obtained revealed that when compared to interpretation guide for evaluating analytical data for management of degraded soils shows that at flood recession, pH (4.9 – 5.48) was strongly acidic, organic carbon (6.1 – 7.6 g/kg) were moderate, TN and P (0.7 – 0.9 g/kg) and (16.2 and 43.2 mg/kg) were very high respectively, Ca and K were also very high in the soil (7.51 – 25.48cmol/kg) and (2470.05 – 3293.79 cmol/kg) respectively, CEC (34.34 – 38.75 cmol/kg) was also very high. The same trend was observed in the level of selected micro nutrients in the soils due to flood recession when compared to available interpretation standard for crop production. Flooding and flood recession actually impacted on soils of the study area by increasing the level of some of the chemical properties and selected micro nutrients of the soils due to influx of materials in the environment by flood water, which the aim of this research is to evaluate impact of flood on Chemical Properties and Selected Micro Nutrients in Soils Southern Ijaw, Bayelsa State.